Multi-factor combined aging characteristic evaluation method for composite insulator material
Through the multi-factor combined aging characteristic evaluation method, including alternating hygroscopic tests and electric-thermal combined aging tests, the problem of the inability of the prior art to evaluate the aging characteristics of composite insulator materials under the electrical-thermal-humid coupling physics is solved, and the composite insulators is realized Comprehensive evaluation of material aging characteristics.
Patent Information
- Application Number
- CN202411712278.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art cannot effectively evaluate the aging characteristics of composite insulator materials under the electrical-thermal-wet coupling physical field, and cannot simulate wet physical factors caused by moisture intrusion.
Multi-factor combined aging characteristics evaluation method is used, including preparing test samples, performing alternating hygroscopic tests and electric thermal combined aging tests, and performing performance testing and evaluation. The test samples included silicone rubber material and mandrel material. The electric-thermal-wet coupling physics was simulated through the set up moisture absorption test and the electric-thermal combined aging test.
It can better meet the need to evaluate the aging characteristics of composite insulator materials in the electrical-thermal-wet coupling physics, and help to more clearly understand the failure laws of composite insulators.
Smart Images

Figure CN119510276A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite insulator performance detection, and in particular to a multi-factor combined aging characteristic evaluation method for composite insulator materials. Background Art
[0002] In recent years, thanks to the development of fiber-reinforced composite materials, composite insulators for high-voltage lines have been widely used. Excellent material properties are the key to ensuring the safe and reliable operation of composite insulators; statistics in the industry show that one of the main manifestations of composite insulator failure is local overheating, and the possible cause of local overheating is the material degradation of the composite insulator under the electric-thermal-humidity coupled physical field. Therefore, evaluating the aging characteristics of composite insulator materials under the electric-thermal-humidity coupled physical field is of great significance for optimizing the structure and performance of composite insulators.
[0003] In the prior art, although there are many methods for testing the aging degree of composite insulator materials, most of these methods cannot well meet the needs of evaluating the aging characteristics of composite insulator materials under the electric-thermal-humidity coupled physical field. The specific reason is that in the current testing methods, a single aging test is usually carried out on the silicone rubber material or core rod material of the composite insulator, and the aged samples are observed and performance tested under normal conditions. This testing method can only examine the aging degree of a single material, and because it is carried out under normal conditions, it cannot simulate the wet physical factors caused by the special working condition of water intrusion. For example, a Chinese patent with publication number CN115184219A provides a composite insulator aging degree evaluation method, which specifically includes step 1: selecting a silicone rubber shed of a composite insulator to be tested as a test sample, step 2: testing the test sample with a filler dispersion meter to obtain the filler distribution on the surface of the test sample, and step 3: judging the aging degree of the composite insulator according to the measured filler distribution. Although this evaluation method can efficiently complete the test of the aging state of the silicone rubber shed, it has the problems of single inspection material and inability to simulate the electric-thermal-humidity coupled physical field.
[0004] In summary, the present invention provides a method for evaluating the multi-factor combined aging characteristics of a composite insulator material. Summary of the invention
[0005] The purpose of the present invention is to provide a method for evaluating the multi-factor combined aging characteristics of composite insulator materials to solve the following problems mentioned in the above background technology: the methods for testing the aging degree of composite insulator materials in the prior art cannot well meet the needs of evaluating the aging characteristics of composite insulator materials under the electric-thermal-humidity coupled physical field.
[0006] The present invention is achieved by adopting the following technical solutions:
[0007] A multi-factor combined aging characteristic evaluation method for composite insulator materials comprises the following steps:
[0008] Step S1: preparing a test sample;
[0009] Step S2: performing a multi-factor combined test on the test sample;
[0010] Step S3: Performing performance test on the test samples after the multi-factor combined test;
[0011] Step S4: evaluating the multi-factor combined aging characteristics of the composite insulator material according to the performance test results and the test conditions of the multi-factor combined test;
[0012] Wherein: in the step S1, the test sample contains silicone rubber material and core rod material; in the step S2, the multi-factor combined test includes a moisture absorption test and an electric and thermal combined aging test performed alternately.
[0013] Furthermore, in step S3, the performance test includes sample dissection observation and in-situ electrical performance test.
[0014] Furthermore, the test sample includes a silicone rubber material layer and a core rod material layer, two sheet electrode structures are arranged between the silicone rubber material layer and the core rod material layer, and the silicone rubber material layer, the two sheet electrode structures and the core rod material layer are cross-linked by hot pressing to form an integrated structure; the two sheet electrode structures are symmetrically arranged with a gap between them, and the two sheet electrode structures respectively form a high-voltage side electrode and a low-voltage side electrode.
[0015] Furthermore, the step S2 includes the following sub-steps:
[0016] Step S2-1: Place the test sample in an oven or boil it in hot water, and set a specific moisture absorption time, moisture absorption humidity or moisture absorption temperature to complete moisture absorption;
[0017] Step S2-2: placing the test sample after moisture absorption into an oven, setting a specific drying time and drying temperature to complete drying after moisture absorption;
[0018] Step S2-3: applying a high voltage to the high-voltage side electrode in the test sample through a high-voltage power supply; grounding the low-voltage side electrode in the test sample through a ground potential;
[0019] Step S2-4: placing the test sample into an oven and setting a specific aging time and aging temperature;
[0020] Among them, step S2-1 to step S2-2 are steps for performing a moisture absorption test, and step S2-3 to step S2-4 are steps for performing an electric and thermal combined aging test; in actual operation, the above steps are cyclically performed according to the required degree of aging.
[0021] Furthermore, carrying out the sample anatomical observation includes the following sub-steps:
[0022] Step S3-o1: Slice the test sample and observe the appearance morphology change, roughness change and discharge trace pores of the test sample with naked eyes;
[0023] Step S3-o2: using an optical microscope and a scanning electron microscope to observe the microstructure of the material at the interface of the test sample;
[0024] Step S3-o3: using infrared spectroscopy and Raman spectroscopy to test the chemical composition of the material at the interface of the test sample.
[0025] Furthermore, when carrying out the in-situ electrical performance test, it includes a conductivity test and a breakdown voltage test; the conductivity test includes the following sub-steps:
[0026] Step S3-c1: using the high-voltage side electrode and the low-voltage side electrode in the test sample as the electrode structure for conductivity testing, and connecting the high-voltage side electrode and the low-voltage side electrode to a DC voltage and a ground electrode respectively;
[0027] Step S3-c2: Connect a resistor in series with the electrode structure, adjust different temperatures and different electric field strengths, and then record the current value and calculate the conductivity data;
[0028] The breakdown voltage test comprises the following sub-steps:
[0029] Step S3-v1: using the high-voltage side electrode and the low-voltage side electrode in the test sample as the electrode structure for the breakdown voltage test, connecting the high-voltage side electrode and the low-voltage side electrode to the power frequency AC voltage and the ground electrode respectively, and using a step-by-step or continuous voltage boosting method to obtain AC breakdown field strength data;
[0030] Step S3-v2: Use the high-voltage side electrode and the low-voltage side electrode in the test sample as the electrode structure for the breakdown voltage test, connect the high-voltage side electrode and the low-voltage side electrode to the DC voltage and the ground electrode respectively, and use a step-by-step or continuous voltage boosting method to obtain DC breakdown field strength data.
[0031] Furthermore, in the step S1, several test samples with the same structure are prepared; in the step S2, several test samples with the same structure are placed in the same humidity environment for a moisture absorption test; and then, the several test samples are connected in parallel and then subjected to an electric-thermal combined aging test, or the electric-thermal combined aging test is performed on several test samples one after another under the same test conditions.
[0032] Furthermore, the interval between the two sheet-like electrode structures is 2 mm to 50 mm, and the thickness of the two sheet-like electrode structures is 0.05 mm to 2 mm.
[0033] Furthermore, in step S2-1, if the test sample is placed in an oven, the moisture absorption humidity range that needs to be set is 50% to 100%, and the moisture absorption time range is ≥1h; if the test sample is placed in hot water for boiling, the moisture absorption temperature range that needs to be set is 50℃ to 100℃, and the moisture absorption time range is ≥10min.
[0034] The beneficial effects achieved by the present invention are:
[0035] A method for evaluating the multi-factor combined aging characteristics of composite insulator materials can be used to complete the evaluation of the aging characteristics of composite insulator materials under the combined action of multiple factors by executing steps S1 to S4, wherein: the test sample contains silicone rubber material and core rod material, so it is not limited to the investigation of a single material; by setting up a moisture absorption test, the wet physical factor caused by the special working condition of water intrusion can be simulated, and an electric-thermal combined aging test alternately performed with the moisture absorption test is set up, thereby forming a multi-factor combined test, and then the electric-thermal-wet coupling physical field can be simulated. Based on this, the method can better meet the needs of evaluating the aging characteristics of composite insulator materials under the electric-thermal-wet coupling physical field, and help to more clearly understand the failure law of composite insulators. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 is a schematic diagram of the overall structure of the test sample according to an embodiment of the present invention;
[0037] Figure 2 is a schematic diagram of the distribution of two sheet-shaped electrode structures in the test sample according to an embodiment of the present invention;
[0038] Figure 3 is a schematic diagram of connecting a plurality of test samples in parallel according to an embodiment of the present invention;
[0039] In the figure: 1. Silicone rubber material layer; 2. Core rod material layer; 3. Sheet electrode structure. DETAILED DESCRIPTION
[0040] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0041] Example 1
[0042] This embodiment provides a method for evaluating the multi-factor combined aging characteristics of a composite insulator material, comprising the following steps:
[0043] Step S1: preparing a test sample containing a silicone rubber material and a core rod material.
[0044] Specifically:
[0045] Please refer to Figure 1 The test sample includes a silicone rubber material layer 1 and a core rod material layer 2, and the silicone rubber material layer 1 and the core rod material layer 2 form a double-layer parallel structure; two sheet electrode structures 3 are arranged between the silicone rubber material layer 1 and the core rod material layer 2, and the two sheet electrode structures 3 form a high-voltage side electrode and a low-voltage side electrode respectively; the silicone rubber material layer 1, the two sheet electrode structures 3 and the core rod material layer 2 are cross-linked by hot pressing to form an integrated structure, which is close to the actual production process of silicone rubber composite insulators.
[0046] Please refer to Figure 2 , the two sheet-like electrode structures 3 are symmetrically arranged with a gap between them; in this embodiment, the two sheet-like electrode structures 3 are in the shape of a rectangle with a semicircular end, and in other embodiments, they can also be in the shape of an arc, a polygon, etc., but it is necessary to avoid defects such as sharp points, burrs and scratches. In addition, the sheet-like electrode structures 3 can be made of metal materials such as copper and aluminum, and the thickness of the two sheet-like electrode structures 3 is 0.05mm to 2mm, and the gap between them is 2mm to 50mm.
[0047] Step S2: performing a multi-factor combined test on the test sample, the multi-factor combined test including a moisture absorption test and an electric-thermal combined aging test performed alternately.
[0048] Specifically:
[0049] This step includes the following sub-steps:
[0050] Step S2-1: Place the test sample in an oven or boil it in hot water, and set a specific moisture absorption time, moisture absorption humidity or moisture absorption temperature to complete moisture absorption.
[0051] In this step, if the test sample is placed in an oven, the moisture absorption humidity range that needs to be set is 50% to 100%, and the moisture absorption time range is 1 hour to several days; if the test sample is placed in hot water for boiling, the moisture absorption temperature range that needs to be set is 50°C to 100°C, and the moisture absorption time range is 10 minutes to several hours.
[0052] Step S2-2: Put the test sample after moisture absorption into an oven, set a specific drying time and drying temperature to dry the surface and surface layer of the test sample, that is, complete the drying after moisture absorption.
[0053] In this step, the drying temperature needs to be set in the range of 50° C. to 100° C., and the drying time needs to be set in the range of 10 minutes to several hours.
[0054] Step S2-3: applying a DC high voltage or an AC high voltage at an industrial frequency to the high-voltage side electrode of the test sample through a high-voltage power supply; and grounding the low-voltage side electrode of the test sample through a ground potential.
[0055] In this step, the high-voltage side electrode in the test sample is connected to the high-voltage end of the high-voltage power supply, and the low-voltage side electrode in the test sample is connected to the ground end of the ground potential; wherein, attention should be paid to anti-corona treatment at the connection point.
[0056] Step S2-4: Place the test sample in an oven and set a specific aging time and aging temperature.
[0057] In this step, the aging temperature needs to be set in the range of 60° C. to the softening temperature of the core rod material.
[0058] During the moisture absorption and drying process, mechanical force should be avoided as much as possible on the electrode structure (i.e., the high-voltage side electrode and the low-voltage side electrode) to avoid excessive force on the electrodes and change of relative position or deformation of the test sample. Steps S2-1 to S2-2 are steps for moisture absorption test, and steps S2-3 to S2-4 are steps for electric and thermal combined aging test; in actual operation, the above steps should be cycled a corresponding number of times according to the required degree of aging.
[0059] Step S3: Performing performance testing on the test samples after the multi-factor combined test, the performance testing including sample anatomical observation and in-situ electrical performance testing; when performing the in-situ electrical performance testing, it includes conductivity testing and breakdown voltage testing.
[0060] Specifically:
[0061] Carrying out sample dissection observation includes the following sub-steps:
[0062] Step S3-o1: Slice the test sample and observe the appearance morphology change, roughness change and discharge trace pores of the test sample with naked eyes;
[0063] Step S3-o2: using an optical microscope and a scanning electron microscope to observe the microstructure of the material at the interface of the test sample;
[0064] Step S3-o3: using infrared spectroscopy and Raman spectroscopy to test the chemical composition of the material at the interface of the test sample.
[0065] Conducting a conductivity test consists of the following sub-steps:
[0066] Step S3-c1: using the high-voltage side electrode and the low-voltage side electrode in the test sample as the electrode structure for conductivity testing, and connecting the high-voltage side electrode and the low-voltage side electrode to a DC voltage and a ground electrode respectively;
[0067] Step S3-c2: Connect a resistor in series with the electrode structure, adjust different temperatures and different electric field strengths, and then record the current value and calculate the conductivity data.
[0068] Conducting a breakdown voltage test includes the following sub-steps:
[0069] Step S3-v1: using the high-voltage side electrode and the low-voltage side electrode in the test sample as the electrode structure for the breakdown voltage test, connecting the high-voltage side electrode and the low-voltage side electrode to the power frequency AC voltage and the ground electrode respectively, and using a step-by-step or continuous voltage boosting method to obtain AC breakdown field strength data;
[0070] Step S3-v2: Use the high-voltage side electrode and the low-voltage side electrode in the test sample as the electrode structure for the breakdown voltage test, connect the high-voltage side electrode and the low-voltage side electrode to the DC voltage and the ground electrode respectively, and use a step-by-step or continuous voltage boosting method to obtain DC breakdown field strength data.
[0071] For example, in this embodiment, multiple control groups are set up to conduct multi-factor combined experiments and performance tests respectively, and the recorded data are as follows:
[0072] Table 1 Multi-factor joint test and performance test data records
[0073]
[0074]
[0075] Step S4: Based on the results of the performance test and the test conditions of the multi-factor combined test, the multi-factor combined aging characteristics of the composite insulator material are evaluated.
[0076] Specifically:
[0077] In this step, the aging degree of the test sample is analyzed based on the results of the performance test. For example, the aging degree of the test sample is analyzed by comparing the conductivity data and breakdown voltage data of samples with different aging degrees in the database; and the test conditions of the multi-factor joint test are combined to comprehensively evaluate the multi-factor joint aging characteristics of the composite insulator material.
[0078] In addition, it should be noted that in order to obtain more reasonable evaluation results and avoid contingency, multiple multi-factor combined tests under the same conditions should be repeated multiple times, and performance tests should be carried out on multiple test samples. Therefore, in this embodiment: in step S1, a number of test samples with the same structure are prepared; in step S2, a number of test samples with the same structure are placed in the same humidity environment for moisture absorption test; then, please refer to Figure 3 , several test samples are connected in parallel to carry out the electric and thermal combined aging test, or several test samples are successively subjected to the electric and thermal combined aging test under the same test conditions.
[0079] In summary, the multi-factor combined aging characteristics evaluation method for composite insulator materials provided in this embodiment can complete the evaluation of the aging characteristics of composite insulator materials under the combined action of multiple factors by executing steps S1 to S4, which can meet the needs of evaluating the aging characteristics of composite insulator materials under the electric-thermal-humidity coupled physical field, and help to more clearly understand the failure laws of composite insulators.
[0080] It should be noted that the parts not described in detail or expanded in the above scheme are all existing technologies, which do not belong to the improvements made by the present invention on the existing technologies, nor do they belong to the protection scope of the technical scheme of the present invention. Therefore, they will not be described in detail in this article.
[0081] Of course, the above contents are only preferred embodiments of the present invention and cannot be considered to limit the scope of the embodiments of the present invention. The present invention is not limited to the above examples, and equal changes and improvements made by ordinary technicians in the technical field within the essential scope of the present invention should all fall within the scope of the patent coverage of the present invention.
Claims
1. A multi-factor combined aging characteristics evaluation method for composite insulator materials, characterized in that: The steps include: Step S1: preparing a test sample; Step S2: performing a multi-factor combined test on the test sample; Step S3: Performing performance test on the test samples after the multi-factor combined test; Step S4: evaluating the multi-factor combined aging characteristics of the composite insulator material according to the performance test results and the test conditions of the multi-factor combined test; in: In the step S1, the test sample contains a silicone rubber material and a core rod material; In step S2, the multi-factor combined test includes a moisture absorption test and an electric-thermal combined aging test that are performed alternately.
2. The multi-factor combined aging characteristics evaluation method for composite insulator materials according to claim 1 is characterized by: In step S3, the performance test includes sample dissection observation and in-situ electrical performance test.
3. The multi-factor combined aging characteristics evaluation method for composite insulator materials according to claim 1 is characterized by: The test sample comprises a silicone rubber material layer (1) and a core rod material layer (2); two sheet electrode structures (3) are arranged between the silicone rubber material layer (1) and the core rod material layer (2); the silicone rubber material layer (1), the two sheet electrode structures (3) and the core rod material layer (2) are cross-linked by hot pressing to form an integrated structure; the two sheet electrode structures (3) are symmetrically arranged with a gap between them; the two sheet electrode structures (3) respectively form a high-voltage side electrode and a low-voltage side electrode.
4. The multi-factor combined aging characteristics evaluation method for composite insulator materials according to claim 1, characterized in that: The step S2 includes the following sub-steps: Step S2-1: Place the test sample in an oven or boil it in hot water, and set a specific moisture absorption time, moisture absorption humidity or moisture absorption temperature to complete moisture absorption; Step S2-2: placing the test sample after moisture absorption into an oven, setting a specific drying time and drying temperature to complete drying after moisture absorption; Step S2-3: applying a high voltage to the high-voltage side electrode in the test sample through a high-voltage power supply; grounding the low-voltage side electrode in the test sample through a ground potential; Step S2-4: placing the test sample into an oven and setting a specific aging time and aging temperature; Among them, step S2-1 to step S2-2 are steps for performing a moisture absorption test, and step S2-3 to step S2-4 are steps for performing an electric and thermal combined aging test; in actual operation, the above steps are cyclically performed according to the required degree of aging.
5. The multi-factor combined aging characteristics evaluation method for composite insulator materials according to claim 2 is characterized in that: Carrying out the sample anatomical observation includes the following sub-steps: Step S3-o1: Slice the test sample and observe the appearance morphology change, roughness change and discharge trace pores of the test sample with naked eyes; Step S3-o2: using an optical microscope and a scanning electron microscope to observe the microstructure of the material at the interface of the test sample; Step S3-o3: using infrared spectroscopy and Raman spectroscopy to test the chemical composition of the material at the interface of the test sample.
6. The multi-factor combined aging characteristics evaluation method for composite insulator materials according to claim 2 is characterized by: When carrying out the in-situ electrical performance test, it includes conductivity test and breakdown voltage test; The conductivity test includes the following sub-steps: Step S3-c1: using the high-voltage side electrode and the low-voltage side electrode in the test sample as the electrode structure for conductivity testing, and connecting the high-voltage side electrode and the low-voltage side electrode to a DC voltage and a ground electrode respectively; Step S3-c2: Connect a resistor in series with the electrode structure, adjust different temperatures and different electric field strengths, and then record the current value and calculate the conductivity data; The breakdown voltage test comprises the following sub-steps: Step S3-v1: using the high-voltage side electrode and the low-voltage side electrode in the test sample as the electrode structure for the breakdown voltage test, connecting the high-voltage side electrode and the low-voltage side electrode to the power frequency AC voltage and the ground electrode respectively, and using a step-by-step or continuous voltage boosting method to obtain AC breakdown field strength data; Step S3-v2: Use the high-voltage side electrode and the low-voltage side electrode in the test sample as the electrode structure for the breakdown voltage test, connect the high-voltage side electrode and the low-voltage side electrode to the DC voltage and the ground electrode respectively, and use a step-by-step or continuous voltage boosting method to obtain DC breakdown field strength data.
7. The multi-factor combined aging characteristics evaluation method for composite insulator materials according to claim 1 is characterized by: In the step S1, a plurality of test samples with the same structure are prepared; In step S2, several test samples with the same structure are placed in the same humidity environment for moisture absorption test; then, several test samples are connected in parallel and then subjected to electric and thermal combined aging test, or several test samples are subjected to electric and thermal combined aging test successively under the same test conditions.
8. The multi-factor combined aging characteristics evaluation method for composite insulator materials according to claim 3 is characterized by: The interval between the two sheet-shaped electrode structures is 2 mm to 50 mm, and the thickness of the two sheet-shaped electrode structures is 0.05 mm to 2 mm.
9. The multi-factor combined aging characteristics evaluation method for composite insulator materials according to claim 4 is characterized in that: In step S2-1, if the test sample is placed in an oven, the moisture absorption humidity range that needs to be set is 50% to 100%, and the moisture absorption time range is ≥1h; if the test sample is placed in hot water for boiling, the moisture absorption temperature range that needs to be set is 50℃ to 100℃, and the moisture absorption time range is ≥10min.
Citation Information
Patent Citations
Method for evaluating aging degree of composite insulator
CN115184219A